Localized corrosion: Passive film breakdown vs. Pit growth stability, Part VI: Pit dissolution kinetics of different alloys and a model for pitting and repassivation potentials. (15th April 2021) - Li, Tianshu; Wu, Jun; Frankel, G.S.
Highlights: Metal dissolution kinetics in saturated pit solution were measured for different alloys. A model for E pit and E rp was established based on pit growth stability. Both E pit and E rp correspond to the critical condition of i diss, max = i diff, crit . Lower metal dissolution rate in pit solution correlates with higher E pit and E rp . Strategy for design of corrosion resistant alloys was proposed. Abstract: The pitting resistance of SS316L, SS304, SS430, and pure Fe was studied in chloride-containing solution. Among these alloys, SS316L exhibits the highest pit initiation rate, but also the highest pitting potential. To explain this phenomenon, the maximum pit dissolution current density ( i diss, max ) of the alloys in saturated pit solution was measured using one-dimensional artificial pit electrodes. A lower i diss, max was found to correlate with higher pitting and repassivation potentials. Based on a recently proposed pitting framework, a conceptual model for pitting and repassivation potentials was established, based on which the effect of i diss, max on pitting resistance was discussed.